Dynamics of the Market for Shares of Medium-Sized Enterprises in the Cluster of US Food Companies with a Minimum Market Capitalization - Bilotserkivskyi, Oleksandr; Kaganovskyy, O. S.; Lyashenko, Vyacheslav (My University, 2023)
The functioning and development of business is closely related to the concept of security. Such security applies both to the direct conduct of certain activities and to the content surrounding the enterprise. Food security is of particular importance in this aspect. This type of security largely determines the economic aspects of the stable activity of various areas in ensuring sustainable interaction between business entities, countries and the population. Therefore, the analysis of the activities of enterprises from the cluster of food companies occupies a special place and is important in making appropriate decisions. Among the various characteristics of the activities of enterprises, attention should be paid to the dynamics of the prices of its shares. This allows you to analyze how the functioning of the business entity itself, and to obtain comparative aspects of such activities in comparison with other companies. In the article, on the example of a number of individual enterprises, a cluster of US food companies is considered. A feature of this consideration is the analysis of the activities of companies with a minimum market capitalization. The work presents a lot of drawings and diagrams. This allows us to understand the course of the study, to consider the activities of medium-sized businesses.
Keywords: data; dynamics; stock market; cluster; capitalization; medium business; statistical analysis; statistical estimates